Fabrication of spatially-variable heterostructured CoCrFeMnNi high entropy alloy by laser processing - Shen, Jiajia (2024)
JS and JPO acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES ) for its financial support via the project UID/00667/2020 (UNIDEMI). JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394 ). This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MSIP) (NRF-2022R1A5A1030054 ). Funding Information: Interestingly, DP-HEA exhibits higher maximum strength (≈570 vs. ≈ 693 MPa) and ductility (≈11.0 vs. ≈ 18.9 %) compared to SP-HEA (refer to Fig. 5 a)). This difference can be mainly attributed to the distinct spatial heterogeneity in the resulting microstructures, leading to different interactions between the soft and hard domains. Typically, in heterogeneous structures, both the soft and hard domains undergo elastic deformation first when subjected to external loading, similar to conventional homogeneous materials. However, as the loading increases, the soft domain will preferentially initiate plastic deformation while the hard domain not, leading to the existence of a mechanical incompatibility. This results in the generation of geometrically necessary dislocations (GNDs) near the interface between the soft and hard domains, which accumulate at the interface and induce hetero-deformation induced (HDI) strengthening [ 38–40]. Theoretically, heterogeneous materials are characterized by significant strength differences between soft and hard domains. The larger the strength differences between domains, the higher mechanical incompatibility, and higher back stresses accumulate in the soft domains, leading to enhanced HDI strengthening and strain hardening. So far, numerous researchers have successfully utilized these strengthening concepts to fabricate spatially heterogeneous structural materials with excellent mechanical properties [ 41–46]. However, the final mechanical properties of the fabricated spatially heterogeneous materials can be affected by a variety of factors, such as alloy composition, purity of the original materials, synthesis methods, and subsequent processing techniques employed in the fabricated spatially heterogeneous structures. Thus, direct one-to-one property comparisons between the present pulsed laser-processed spatial heterogeneous materials (SP-HEA and DP-HEA) and other spatial heterogeneous materials produced using alternative fabrication methods would lead to biased comparisons. Therefore, in this case, the comparison with spatially heterogeneous materials made by other processes is not performed. Instead, a comparative analysis was performed, focusing on the same original as-rolled CoCrFeMnNi used as a benchmark for mechanical properties [37]. The present results demonstrate that SP-HEA and DP-HEA exhibit superior performance in terms of ductility (18.9% vs. 11.0% vs. 9.5%, for SP-HEA, DP-HEA, and as-rolled CoCrFeMnNi, respectively), albeit with reduced strength when compared to the as-rolled CoCrFeMnNi (693 MPa vs. 570 MPa vs. 947 MPa), showcasing the potential application of these two heterostructured materials (SP-HEA and DP-HEA) for structural applications where depending on the expected loading conditions, one can chose either processing methodology. An intriguing observation arises from the tensile stress-strain curves, specifically in the elastic deformation stage, where the slope of SP-HEA is discernibly lower than that of DP-HEA. This discrepancy suggests that, under equivalent external loading, SP-HEA undergoes a more substantial deformation. To elucidate this behavior, delving into the dynamics of loading transfer and the dimensions of the load-bearing area for both SP-HEA and DP-HEA is necessary. In materials featuring both soft and hard regions, the initial load during external loading is borne by the softer regions due to their inherent characteristics. As these soft regions yield, the load gradually transfers to the harder regions. Additionally, considering the load-bearing area, a larger object subjected to the same external load experiences relatively lower force per unit area. Therefore, to achieve an equivalent deformation, the load applied to the larger load-bearing area must surpass that applied to the smaller force-bearing area. Applying these principles to SP-HEA and DP-HEA, the stress-strain curve reveals a lower elastic slope for SP-HEA, indicating higher deformation under the same external load. This can be primarily attributed to the fact that the area of relatively soft regions in DP-HEA is nearly twice that of SP-HEA. When subjected to the same external load, the initially stressed areas—represented by the FZ—exhibit varying force per unit areas due to the doubled FZ area in DP-HEA. Consequently, the external load required to induce yielding in the soft region of DP-HEA is significantly greater than that in SP-HEA, thereby contributing to the observed difference in elastic slopes. Returning to the current work, the strength (hardness) difference between the soft and hard domains in SP-HEA is significantly larger than in DP-HEA, 100 vs 252 HV0.2, respectively. Therefore, the mechanical performance of SP-HEA would be expected to be better than that of DP-HEA. However, DP-HEA demonstrates superior mechanical properties in terms of both strength and plasticity than SP-HEA. An initial inference is that the large strength difference (≈210 vs. ≈400 HV0.2) between the soft domain (FZ) and the hard domains (rolled BM) in SP-HEA results in massive mechanical incompatibility at the interface. The highly concentrated strain gradient leads to a large accumulation of dislocations at the interface, inducing stress concentration and crack initiation, ultimately resulting in failure at the soft-hard interface. This inference is supported by the observed fracture locations of SP-HEA, as indicated in Fig. 5 b1). On the contrary, the improved mechanical performance of DP-HEA can be attributed to its relatively uniform distribution of heterogeneity at the microstructure level, with a small strength difference between the hard and the soft domains (≈230 vs ≈ 210 HV0.2). This minimizes the mechanical interactions between them and reduces the potential for stress concentrations. Additionally, this more homogeneous microstructure distribution allows for better stress absorption and dispersion, enhancing the material's toughness and ductility. These factors collectively contribute to the improved mechanical properties of DP-HEA, which is further corroborated by the observed ductile fracture mode with numerous dimples on the fracture surface of Fig. 5 b2). Here, a special explanation is needed for the states of stress concentration in heterostructured materials. It is known that during the plastic deformation of heterostructured materials, the hetero zones deform in-homogeneously, generating back stresses in the soft zones and forward stresses in the hard zones. Back stress originates from the accumulation of dislocations in the soft zone, which will act to impede dislocation slip in the soft zone promoting a strain-hardening effect. Forward stresses are created in the hard zone due to stress concentrations at the zone boundary caused by dislocation pileup. For heterostructured materials, HDI strengthening is typically the result of the synergistic effect of both back and forward stresses: the back stresses act to enhance the HDI strengthening, while the forward stresses act to limit the HDI strengthening by assisting the plastic deformation in the hard zones. Therefore, compared to DP-HEA, where the difference between the soft and hard gradients is relatively small (≈100 vs ≈ 252 HV0.2), the high dislocation density generated in the soft zone of SP-HEA (refer to Fig. 2 b)) causes a high stress concentration that occurs at the soft/hard interface, which inevitably generates high forward stresses in the hard domain. As a result, the higher forward stresses in SP-HEA weaken the HDI strengthening in a more abrupt way in DP-HEA. Therefore, a significant difference in hardness between the soft and hard domains can lead to high stress concentrations at the interface, increasing the risk of crack initiation and eventually fracture. Additionally, excessive stress concentration can induce high forward stresses within the hard domain, which in turn weakens the HDI strengthening effect. Thereby, the magnitude of hardness difference is just one factor affecting HDI strengthening, and the actual material performance is determined by the interaction of multiple factors. Thus, the exceptional mechanical properties observed in DP-HEA can be attributed to the combined effects of multiple factors. While the introduction of back stresses theoretically suggests the possibility of stress concentration, DP-HEA exhibits a more balanced microstructural distribution, leading to improved stress absorption and dispersion. Additionally, the smaller strength disparities between the soft and hard domains contribute to reduced mechanical incompatibility. In DP-HEA, there exists a relatively moderate hardness difference between the soft and hard domains, effectively reducing the back stress from the hard zone. Furthermore, the processing conditions, involving an optimized microstructure, play a crucial role in alleviating this stress concentration effect. These conditions further enhance the material's strength and ductility. This complex interplay of factors highlights the intricate relationship between microstructure and mechanical performance in heterogeneous materials. In addition, through a comparative analysis of two spatially heterogeneous materials (SP-HEA and DP-HEA) prepared using different laser processing techniques, it has been confirmed that the applicability of the back stresses strengthening effect (HDI strengthening) depends on the specific characteristics of the material and the associated processing conditions. Here, it is worth mention that, the current work was focus on comparing and analyzing the microstructural characteristics and mechanical properties between the two distinct spatially heterogeneous structures (SP-HEA and DP-HEA). However, future endeavors will primarily concentrate on systematically investigating a broader range of laser parameters to fabricate spatially-variable heterostructured CoCrFeMnNi high entropy alloy through laser processing. This expanded exploration aims to gain a more comprehensive understanding of how different laser parameters impact the microstructure and mechanical properties of CoCrFeMnNi high entropy alloy.JS and JPO acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JS, ACB and JPO acknowledges the funding of CENIMAT/i3N by national funds through the FCT-Fundação para a Ciência e a Tecnologia, I.P. within the scope of Multiannual Financing of R&D Units, reference LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020. JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394). This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MSIP) (NRF-2022R1A5A1030054). Publisher Copyright: © 2024 The Author(s)